Violence in the Family (Case Study in Kampung Nusantara Dompak, Sei Jang Village, Bukit Bestari District, Tanjungpinang City) - Julesna Fransiska Hutabarat; Emmy Solina; Taufiqqurrachman Taufiqqurrachman (Faculty of Social and Political Science Universitas Maritim Raja Ali Haji, Indonesia, 2023)
Within every social group, there is a possibility of acts of violence, including the family. The family is the group with the highest number of occurrences of acts of violence. There are driving factors that lead to acts of violence in the family, such as the economy, culture, legal awareness regarding violence in the family, law enforcement, and the social environment. There are phenomena related to acts of violence in the family, both physical and psychological. Researchers used a qualitative approach method and a purposive sampling technique to determine informants. Seventeen people became informants in this study, and data collection methods were in the form of observation, interviews, and documentation. The study utilized the theory of Family Roles and Functions. The results of this study revealed that violence in the family in Kampung Nusantara Dompak occurred due to the habit of alcohol consumption by husbands or fathers, leading to a negative impact on the roles and functions of the family.